Study of Microbial Desalination Cell Performance; Power Generation and Desalination Efficiency using Pure Oxygen in a Cathode Chamber - Abd-almohi, Hussein H.; Alismaeel, Ziad T.; M-Ridha, Mohanad J. (Al-Khwarizmi Engineering Journal, 2022)
Microbial Desalination Cell (MDC) is capable of desalinating seawater, producing electrical power and treating wastewater. Previously, chemical cathodes were used, which were application restrictions due to operational expenses are quite high, low levels of long-term viability and high toxicity. A pure oxygen cathode was using, external resistance 50 and 150 k Ω were studied with two concentrations of NaCl in the desalination chamber 15-25 g/L which represents the concentration of brackish water and sea water. The highest energy productivity was obtained, which amounted to 44 and 46 mW/m3, and the maximum limit for desalination of saline water was (31% and 26%) for each of 25 g / L and 15 g / L, respectively, when using an external resistance of 150 KΩ. At 50 KΩ, 13 and 12 mW/m3 were obtained, and the maximum desalination limit were 20% and 2% when using 25 g / L and 15 g / L, respectively. The concept of the mixing process was introduced in the desalination chamber to improve the performance of the system, where the highest energy productivity was obtained, which amounted 45 and 47 mW/m3, and the percentage of salt removal in the desalination chamber were 40% and 55% when using 15 g/L and 25 g/L and 150 KΩ, respectively. This study demonstrated a promising approach to using the mixing process in the desalination room in order to increase the desalination and electrical productivity.